Optimization of droplet digital polymerase chain reaction (ddpcr) for DNA copy number variation analysis of CNV esv27061 in young adults with higher blood pressure in young adults with higher blood pressure - Shaik Alaudeen, Siti Radziah; Abdullah, Aszrin; Mohd Shah, Azarisman Shah; A.Talib, Norlelawati (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia., 2017)
Introduction: Copy number variation (CNV) caused by changes in DNA sequences of 1000 or more bases is implicated with susceptibility to common diseases. A study on CNV esv27061 among hypertensive Australian adults reported association with high blood pressure (BP). In Malaysia,no study on CNV among hypertensive young adults is available. Thus,this investigation aimed to assess the CNV esv27061 of young Malaysian adults with high blood pressure using optimized ddPCR.